Beechain: aplicando blockchain hyperledger iroha para rastrear mel de abelha - Barbosa, Francisco Ronald Araújo (2023)
Product traceability is a growing concern for increasingly demanding consumers regarding the origin and quality of what they are consuming. However, among the main challenges associated with new consumer market demands, the traceability and certification process can be highlighted. Often, traditional processes are expensive, bureaucratic, and subject to fraud and counterfeiting. In this work, we present a more economical and less bureaucratic solution, based on Hyperledger Iroha Blockchain, to reliably track and certify the honey production chain. The proposed solution consists of a traceability system, called Beechain, composed of smart contracts that record important information about the production process, such as the origin of the honey, production and transportation conditions, among other relevant data, such as date and time of harvest, beehive location, honey volume, and logistics data. We demonstrate in this study that Blockchain technology makes the traceability process more reliable, as the information recorded on the network cannot be tampered with. In addition, the results obtained suggest that the adoption of Blockchain technology increases the integration of the production chain links and transparency in transactions throughout the process, which can lead to greater consumer confidence in the products purchased.